Brand fidelity: a relationship maintenance perspective. Issue 6 (November 2018) - Grace, Debra; Ross, Mitchell; King, Ceridwyn
Abstract An in-depth literature review associated with consumer/brand research provides the foundation for this paper through explicating the evolution of this important research stream. The literature findings highlight significant challenges in the conceptualization and measurement of key consumer-related constructs such as brand loyalty, brand commitment and brand love. Drawing upon these findings, the authors propose that relationship maintenance mechanisms (i.e. cognitive and behavioural) provide the key to measurement and prediction of consumer/brand relationship strength. On this basis, this paper offersbrand fidelity as a novel approach in understanding how consumers demonstrate their love and commitment for the brand through engaging, subconsciously or otherwise, in relationship maintenance cognitions and behaviours. Defined asthe consumer's faithfulness to a brand partner demonstrated by an aggregate of behaviours (i.e. accommodation/forgiveness, willingness to sacrifice )and cognitions (i.e. derogation of alternatives, cognitive interdependence and positive illusions )that maintain relationship stability and durability, brand fidelity provides a solid foundation for future research offering significant value to academics and brand practitioners alike.